Validity and Realibity of the Turkish form of the Emotion Regulation Questionnaire - Tarik TOTAN (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Objective: The purpose of the present study was investigated the psychometric properties of the Turkish form of the Emotion Regulation Questionnaire (ERQ) as reappraisal and suppression via classical test theory. Method: The research was conducted 159 (52.5%) female and 144 (47.5%) male, and total 303 Turkish young adult. The participants age mean was 20 years and 11 months. The ERQ, the Emotional Self-Efficacy Scale, the Regulatory Emotional Self-efficacy Scale, the Satisfaction of Life Scale and Oxford Happiness Scale (Short form) were used for data collection tools. Exploratory factor analysis, parallel analysis, and confirmatory factor analysis were used for investigation of the psychometric properties of the ERQ. Also, criterion-related validity, test-retest validity, and internal consistency were used for analysis. Results: The exploratory factor analysis results showed that item factor loadings of ERQ were between .53 and .75. Item-total correlations were above the .33. All items were determined by separate groups within the upper and lower levels of emotion regulation. The confirmatory factor analysis results showed that the original version of the ERQ confirmed on the Turkish version. Internal consistency coefficients of the scale were found .78 for cognitive reappraisal, .71 for suppression, and .72 for total. Test-retest results loaded above .65. Conclusion: The research showed that ERQ has got psychometric quality in Turkish for using as reappraisal and suppression factors. Consequently, the scale can be used in person or group focused psychotherapy and research. [JCBPR 2015; 4(3.000): 153-161]